DISABILITY CAUSED BY HIP JOINT INJURIES AMONG THE ADULT POPULATION OF MOSCOW FOR THE PERIOD OF 2013-2019 - M.V. Kovrizhnykh; N.S. Zapariy; E. E. Achkasov; V.S. Solovev; A.G. Samusenko (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The study found out that for the 2013-2019 period saw a decrease in the incidence of primary disability caused by hip joint injuries among the adult population of Moscow. The level of primary disability averaged 0.09 ± 0.03 per ten thousand of adult population. In the structure of disability caused by injuries of the lower limbs the hip joint injuries accounted for 10.5% over the period. The age structure was dominated by disabled people above the working age with a tendency to decrease their share. In the nosological structure people disabled as a result of the femoral neck fractures (46.2%) and the femur fractures (29.3%) prevailed. In the structure of people who was the firstly recognized as disabled the disabled people of groups II and III prevailed (with a large proportion of the disabled of group III and the lower share of the disabled people of group II). The proportion of people with disabilities in group I is the smallest, and it tends to decrease over the period. Among people above the working age the disabled people of groups I and II prevailed while among people of the working age the disabled of groups II and III prevailed.The incidence of repeated disability of this contingent was also characterized by a downward trend. The level of repeated disability averaged 0.11 per ten thousand of population. The share of people repeatedly recognized as disabled due to injuries of the lower limbs was 8.5%. The structure was dominated by people with disabilities caused by femoral neck and femur fractures. The period saw an increase in the proportion of disabled people of working age. The disabled people of group III with a tendency to increase their share and disabled people of group II with a tendency to decrease their share prevailed, and the number of disabled people of group I decreased.